Pertanggungjawaban Pidana Anak di Bawah Umur dalam Kasus Pencurian (Perbandingan Hukum Islam dan Hukum Positif) - Mafakhir, Muhammad Nafidlul (UIN Sunan Kalijaga Yogyakarta, 2016)
The issue of the responsibility of minors and their criminal sanctions is an interesting topic to discuss, considering that there is a lack of uniformity in both positive law and Islamic criminal law. The mindset of many law enforcement officials is currently centered on the understanding that all criminal cases must still be included in the realm of punishment (directly processed through litigation), even though these cases are crimes with relatively small losses or minor crimes. This is legal in the theory of positivism, provided that the act is clearly accommodated in the law (the principle of legality is met). However, not infrequently this process actually hurts the sense of justice in society. This article is a literature research with a descriptive analysis research method. Furthermore, the existing data is described and analyzed carefully in order to find the right conclusions. The results of this study are based on the positive law of the Child in view of Law no. 3 of 1997 concerning Juvenile Court is a person who has not been able to take responsibility for his actions, whether it is a criminal act or an act prohibited by the regulations in force in society. Children who are underage are considered as people who are unable to know the consequences of their actions because their thinking development has not yet reached the level of adults. So that children who can be punished are children whose age limit has been determined in the law. Meanwhile, according to Islamic law, if the perpetrator of the theft is a child or a madman, he cannot be sentenced to hadd cutting off his hands, based on hadith. Because cutting hands is a form of punishment, while punishment is carried out because of a crime. Meanwhile, the actions of a child who is a madman are not called a crime.